The undesirability of randomized income taxation under decreasing risk aversion - Martin Hellwig (Max Planck Institute for Research on Collective Goods, 2005)
For the standard specification of the utilitarian optimal income tax problem with hidden characteristics, the paper shows that randomized tax schemes are undesirable if preferences exhibit a property of weakly decreasing risk aversion according to the multidimensional risk aversion concept of Hellwig (2004). The property of decreasing risk aversion also implies uniqueness of the optimal income tax schedule and continuity in cases where the type distribution has a continuous density.
Keywords: H21; 330; Optimal Income Taxation; Randomized Incentive Schemes; Nonincreasing Risk Aversion; Einkommensteuer; Optimale Besteuerung; Risikoaversion; Ökonomischer Anreiz; Theorie